Water Resources Management in the Ganges Basin : A Comparison of Three Strategies for Conjunctive Use of Groundwater and Surface Water - Khan, Mahfuzur R.; Voss, Clifford I.; Yu, Winston; Michael, Holly A. (Springer, 2016)
The most difficult water resources management challenge in the Ganges Basin is the imbalance between water demand and seasonal availability. More than 80 % of the annual flow in the Ganges River occurs during the 4-month monsoon, resulting in widespread flooding. During the rest of the year, irrigation, navigation, and ecosystems suffer because of water scarcity. Storage of monsoonal flow for utilization during the dry season is one approach to mitigating these problems. Three conjunctive use management strategies involving subsurface water storage are evaluated in this study: Ganges Water Machine (GWM), Pumping Along Canals (PAC), and Distributed Pumping and Recharge (DPR). Numerical models are used to determine the efficacy of these strategies. Results for the Indian State of Uttar Pradesh (UP) indicate that these strategies create seasonal subsurface storage from 6 to 37 % of the yearly average monsoonal flow in the Ganges exiting UP over the considered range of conditions. This has clear implications for flood reduction, and each strategy has the potential to provide irrigation water and to reduce soil waterlogging. However, GWM and PAC require significant public investment in infrastructure and management, as well as major shifts in existing water use practices; these also involve spatially-concentrated pumping, which may induce land subsidence. DPR also requires investment and management, but the distributed pumping is less costly and can be more easily implemented via adaptation of existing water use practices in the basin.